2022
DOI: 10.3390/app12031441
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of Spent Grain from Malt Whisky in the Spelt Pasta Formulation: Modelling and Optimization Study

Abstract: Although durum wheat flour is conventionally used to produce pasta, in this study, emphasis was placed on the use of spelt flour in the formulation of the pasta recipe, with the replacement with spent grain obtained from distilleries for its content of fiber and protein. D-optimal design was used to optimize the influence of spent grain addition for the quality attributes of spelt pasta. In order to optimize the spelt pasta matrix, the spent grain content was varied (5%, 10%, 15%, and 20%) so that all response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
(101 reference statements)
1
1
0
Order By: Relevance
“…The total dietary fiber content was higher in the wafer sample (11.64% ± 0.04%) compared to the control sample (9.82% ± 0.03%) due to the addition of spent grain that contains a higher amount of fiber; the same trend was observed in study reported by Chetrariu and Dabija, 2022 [36].…”
Section: Resultssupporting
confidence: 82%
“…The total dietary fiber content was higher in the wafer sample (11.64% ± 0.04%) compared to the control sample (9.82% ± 0.03%) due to the addition of spent grain that contains a higher amount of fiber; the same trend was observed in study reported by Chetrariu and Dabija, 2022 [36].…”
Section: Resultssupporting
confidence: 82%
“…Pasta is a ready-to-eat product made from durum wheat [ 79 ]; however, lately it is also obtained from other flours, flour mixtures with or without additional vegetables or other by-products, resulting in quality products that retain a good consistency after cooking. Several researchers have investigated the partial replacement of flour with ingredients from agro-industrial by-products to make pasta [ 80 , 81 , 82 , 83 , 84 ]. The increasing worldwide consumption of pasta is due to its high digestibility, slow carbohydrate release, relatively low glycemic index compared with bread, pizza or other cereal products, high shelf life, versatility and ease of cooking [ 56 ].…”
Section: Possible Uses Of Spent Grain In Food Productsmentioning
confidence: 99%
“…These findings demonstrate that spent grain can be successfully included in a fortified pasta recipe to provide highquality outcomes. Because they may enhance the products' nutritional value and have a lower glycemic index than pasta made with durum wheat white flour, spent grain flours can be employed in food compositions [6]. According to the results of another study, the inclusion of spent grain in the wafer formulation produced goods with a high level of acceptance, altered batter texture, enhanced all parameters, and only lowered adhesiveness.…”
mentioning
confidence: 99%